Peran strategis komite sekolah dan gaya kepemimpinan kepala sekolah dalam optimalisasi mutu layanan pendidikan di sekolah menengah atas - Anggraini, Widya Dwi; Syoviana, Elvi; Agustian, Hesti; Hasan, Alfadila; Putra, Harpendri Eko; Syam, Fadhly (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to analyze the partial and simultaneous influence of the School Committee and the Principal’s Leadership on the quality of education at SMA Negeri 1 Tiumang. The research is grounded in the fact that synergy between these two stakeholders has not been fully optimized to improve educational services, as mandated by Law No. 20 of 2003 on the National Education System. A mixed-method approach was applied, combining a quantitative descriptive design and qualitative exploratory analysis. Data were collected through questionnaires, interviews, observations, and documentation from 43 respondents consisting of teachers, education staff, school committee members, and parents. Regression analysis revealed that, partially, the School Committee significantly influenced educational quality by 46.2%, while the Principal’s Leadership contributed 33%. Simultaneously, both variables accounted for 49.9% of the variation in educational quality, indicating a strong synergistic effect but also suggesting that 50.1% is influenced by other factors such as teacher competence, school culture, and policy support. The study concludes that strengthening the role of the school committee and adopting a transformative leadership style are key to improving educational quality. Strategically, this implies the need for regular communication forums, clear role distribution, and cross-stakeholder collaboration. This research contributes empirical evidence from a local context on the strategic importance of partnerships within Indonesia’s school-based management framework.